رواة الحديث من أهل مأرب إلى نهاية القرن الثالث الهجري - سند، حامد حمود غالب (جامعة إقليم سبأ, 2019)
انتظمت دراسة هذا البحث "رواة الحديث من أهل مأرب إلى نهاية القرن الثالث الهجري" بالجمع والدراسة لأحوال الرواة، وذلك بذكر أقوال أئمة المحدثين في كل راوي من الرواة المذكورين في طيات البحث وذكر بعض أحاديث هؤلاء الرواة فكانت الدراسة تتركز حول ذكر مكانة اليمن وفضائل أهلها: كما اشتملت على التعريف بمدينة مأرب، ومكانتها بتي مدائن اليمن: واشتملت أيضا على ذكر الرواة من أهل مأرب الذين هم من الصحابة: إذ وصل الباحث إلى أن عددهم ثلاثة كلهم يعود أصلهم إلى مأرب، وشملت ذكر الرواة من أهل مأرب الذين هم من "التابعين" إذ وصل الباحث إلى أن عددهم تسعة رواة كلهم يعود أصلهم إلى مأرب، وجميعهم تفاوتت رتبهم بين الاحتجاج والاعتبار مع كونهم من أهل الصدق، ثم شملت ذكر الرواة من أهل مأرب الذين هم من "أتباع التابعين" إذ وصل الباحث إلى أن عددهم ستة رواة كلهم يعود أصلهم إلى مأرب، وجميعهم ثقات ممن تقبل روايتهم سواء للاحتجاج أو الاعتبار، ما عدا واحدا وهو فضالة بن سعيد المآربي فهو ضعيف لكن ضعفه هذا محتمل عند المحدثين إذا اعتضد حديثه بغيره: وأخيرا ختمت الدراسة بذكر أهم النتائج التي توصل إليها الباحث، وقد ذيلت الدراسة بذكر أهم المصادر والمراجع التي اعتمدت عليها. والحمد لله الذي أعطي من الإنعام والإكرام ما يستحق على فضله وكرمه فله الحمد أولا وأخيرا. والله ولي الهداية والتوفيق...
This study was performed through collecting and studying the situations of the narrators. The research presented what the Imams of the narrators said about the narrator under research. It presented some of the Hadiths of these narrators as well. The research also included a description of Ma’rib city, and its position among the cities of Yemen. It also mentioned the narrators from the people of Ma’rib who are from Al- Sahaba “the companions of our prophet PBUH" where the researcher reached that there are three who are of Ma’rib origin. The research also mentioned the narrators from the people of Marib who are Tabi’in “Followers” where the researcher reached that there are nine narrators who are of Ma’rib origin. The ranks of this group of narrators varied between the ones whose narration is taken as evidence or consideration with being people of honesty. The research included the narrators of the people of Marib who are "followers of the followers" as well. The researcher reached that the number of the narrators or are from Ma’rib origin and belong to this group are six. They are all trusted except for Fadala bin Said Al Marabi who is considered to be weak; but this weakness is only possible for the modernists the Hadith is supported by other narrators. The study was concluded by mentioning the most important findings, and appended with the most important sources and references.
Keywords: السنة النبوية -- علم الحديث -- علماء الحديث -- رواة الحديث -- أهل مأرب